Design of trajectories and torques by parameter optimization for the bench press exercise on a Smith machine - Sánchez-Salinas, Silvia; García-Vallejo, Daniel; López-Martínez, Javier; Muyor, José M. (Mechanism and machine theory, 2021)
•The dynamics of the bench press exercise is simulated by optimization.•Barbell trajectory, shoulder and elbow torques are optimized.•Dynamic effort and mechanical power cost functions are investigated.•Optimized performance of the exercise is design for endurance and safe realization.•Optimized trajectories are compared to test session experimental results. [Display omitted] The bench press exercise on a Smith machine, frequently used in training programs, can be analyzed as a redundantly actuated biomechanical system. In this exercise, a simplified model having one degree of freedom, actuated at the shoulder and the elbow, provides a meaningful representation of its dynamics. Due to the actuation redundancy, many different combinations of actuations that lead to the same motion can be found. The present optimization framework for the bench press exercise is intended at understanding the appropriate performance of this exercise when it is used to gain endurance or to perform the exercise in the safest manner, that is, avoiding overloads. The dynamic simulation is solved by parameter optimization and direct collocation. The kinematics of the bench press exercise performed by a trained subject and recorded with an electro-goniometer is used as a reference motion for the optimization. The results show that it is possible to mathematically obtain better realizations of the exercise, what suggests the potential of this methodology in the design of training programs in sports or rehabilitation exercises.